2015
DOI: 10.1002/mar.20788
|View full text |Cite
|
Sign up to set email alerts
|

Who Buys Oddly Shaped Food and Why? Impacts of Food Shape Abnormality and Organic Labeling on Purchase Intentions

Abstract: Even without official quality standards, food retailers generally do not offer abnormally shaped food based on the assumption that consumers reject food that deviates physically from some norm. Because this practice contributes significantly to food waste, the current study tests this assumption experimentally. A representative sample of 964 Danish consumers indicated their purchase intentions for two fruits and two vegetables with varying levels of food shape abnormality (normal, moderately abnormal, and extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
126
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(175 citation statements)
references
References 75 publications
9
126
0
8
Order By: Relevance
“…This is interesting especially, when compared to results from Loebnitz et al [17] who found out that participants purchased significantly less FaVs when they were extremely misshaped. This difference could be due to differences in how participants were presented with the products: photographies of one single real FaV for Loebnitz et al [17] while we presented them with several 3D virtual products they could manipulate.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…This is interesting especially, when compared to results from Loebnitz et al [17] who found out that participants purchased significantly less FaVs when they were extremely misshaped. This difference could be due to differences in how participants were presented with the products: photographies of one single real FaV for Loebnitz et al [17] while we presented them with several 3D virtual products they could manipulate.…”
Section: Discussionmentioning
confidence: 45%
“…4. Nevertheless, we compared to the real pictures used in [17] as extremely abnormal FaVs, our "heavily" misshaped FaVs did not seem unrealistic. It would prove beneficial to be able to compare results using both real and 3D virtual FaVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the "food losses", a recent trend consists of selling abnormal (i.e., non-standards) FaVs by emphasizing on organic or pro-environmental considerations [21]. Yet, marketing studies aiming to study the impact of abnormal FaVs on consumer behaviors in retail settings are difficult to perform since (i) such FaVs are not always available, (ii) their appearance is time dependent.…”
Section: Introductionmentioning
confidence: 99%
“…They were then asked how likely they were to purchase each of the options. The results showed that extreme abnormalities in fruits and vegetables did influence the consumer intent to purchase and they showed a preference for less blemished produce, or normal produce (Loebnitz et al, 2015). This desire for produce with no imperfections and an increase in the customer's willingness to pay for organic was also found in a study conducted by Chengyan…”
Section: B Imperfectionsmentioning
confidence: 61%